2009
DOI: 10.1128/mcb.00286-09
|View full text |Cite
|
Sign up to set email alerts
|

POT1 Association with TRF2 Regulates Telomere Length

Abstract: Deleting the OB folds encoding the telomeric single-stranded DNA (ssDNA)-binding activity of the human telomeric protein POT1 induces significant telomere elongation, suggesting that at least one critical aspect of the regulation of telomere length is disrupted by this POT1 ⌬OB mutant protein. POT1 is known to associate with two proteins through the protein interaction domain retained in POT1⌬OB -the telomeric doublestranded DNA-binding protein TRF2 and the telomere-associated protein TPP1. We report that intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 78 publications
3
22
0
Order By: Relevance
“…Telomere length phenotypes of POT1/TPP1 knockdown in human cells are controversial (Colgin et al 2003;Veldman et al 2004), and deletion of pot1 + or tpz1 + in fission yeast leads to telomere deprotection. These observations support the proposal that inhibition of telomerase through integration of telomere length information is transduced from the dsDNA-binding TRF1 complex, including TRF2, TIN2, and TPP1, to the telomere terminus through recruiting POT1 to the very end, thereby controlling telomere accessibility to telomerase (Marcand et al 1997;Loayza and de Lange 2003;Barrientos et al 2008;Kendellen et al 2009). Alternatively, one or more shelterin components could also directly act on telomerase to enforce their negative roles.…”
Section: A Model For the Nonextendible Telomeric Statesupporting
confidence: 72%
“…Telomere length phenotypes of POT1/TPP1 knockdown in human cells are controversial (Colgin et al 2003;Veldman et al 2004), and deletion of pot1 + or tpz1 + in fission yeast leads to telomere deprotection. These observations support the proposal that inhibition of telomerase through integration of telomere length information is transduced from the dsDNA-binding TRF1 complex, including TRF2, TIN2, and TPP1, to the telomere terminus through recruiting POT1 to the very end, thereby controlling telomere accessibility to telomerase (Marcand et al 1997;Loayza and de Lange 2003;Barrientos et al 2008;Kendellen et al 2009). Alternatively, one or more shelterin components could also directly act on telomerase to enforce their negative roles.…”
Section: A Model For the Nonextendible Telomeric Statesupporting
confidence: 72%
“…The actual length of the telomeres varies in various species and also within mammals. TRF1 and TRF2 bind the doublestranded (TTAGGG)n repeats of telomeres while POT1 binds to 3' single-stranded G overhangs (Broccoli et al 1997;Smith et al 1998;Ye and de Lange 2004;de Lange 2005;Xin et al 2007;Kendellen et al 2009;Abreu et al 2010). Rap1 was discovered as a TRF2 interacting factor and named such due to its sequence homology with the yeast Rap1 (Li et al 2000).…”
Section: Diverse Roles Of Shelterin Proteinsmentioning
confidence: 99%
“…Shelterin is composed of six core members that include TRF1, TRF2 (Telomeric Repeat binding Factor 1 and 2), TIN2 (TRF1-and TRF2-Interacting Nuclear Factor 2), POT1 (Protection Of Telomeres 1), TPP1 (formerly known as TINT1, PTOP or PIP1) and RAP1 (Repressor/Activator Protein 1) (Broccoli et al 1997;Smith et al 1998;Ye and de Lange 2004;de Lange 2005;Xin et al 2007;Kendellen et al 2009;Abreu et al 2010). Three members of this complex, TRF1, TRF2 and POT1, bind directly to telomeric DNA repeats and anchor the rest of the complex along the length of the telomeres.…”
Section: Diverse Roles Of Shelterin Proteinsmentioning
confidence: 99%
“…It has been shown that the ACD-POT1 sub-complex also has a higher binding affinity to ssDNA than POT1 does on its own [143]. Literature shows that if the function of POT1 is inhibited the length of telomeres is increased through telomerase activity, indicating that this subcomplex is able to regulate the elongation of chromosome ends [144][145][146][147][148]. In our study, we show that missense mutations in the OB-domains of POT1 result in an elongation of telomeres in carriers.…”
Section: Chapter 8 General Discussion and Future Directionmentioning
confidence: 48%